The politics of television the impacts and influences of advertisements endorsed by political figures on the opinion of UP Baguio students as voters - Ansagay, Charito S.; Salvador, Glenda S. (2003)
This research has the title, "The Politics of Television: The Impacts and Influences of Advertisements Endorsed by Political Figures on the Opinion of UP Baguio students as voters". This study contains thirty-five pages including diagrams and tables. The objective of the study is to know if the advertisements of politicians enhance their political careers and images which may therefore influence the opinion of voters. The study has also the aim to analyze the content of the two advertisements namely Ariel Laundry soap which Legarda endorses and Ginebra San Miguel Beer which Jaworski endorses on the other hand. Through these analyses, the researchers assessed the factors in the advertisements, which therefore helped them measures how opinion of voters were influenced. The findings of the study showed that the familiarity of the respondents with the advertisements is very high. Therefore, the researchers concluded that the rate of publicity of the endorsers, Legarda and Jaworski is also very high. Although these findings are true, it was found out that it doesn't follow that the advertisements enhanced the political careers of the two endorsers. It was also found out that the respondents believed that the exposures of Legarda and Jaworski on advertisements lead to their advantage in their campaigns but the respondents were not convinced to vote for them. Most of the respondents' opinion in voting were not affected but might lead to persuasion of voters. The researchers used content analysis in the study and convenience sampling technique in the survey method. The survey material used were questionnaires while the analysis of data was done quantitatively. The study has 100 respondents who were students of UP Baguio, aged 18-21 and are voters. After conducting the study, the researchers recommend to the voters to look at the quality of politicians to vote, while the politicians should be responsible in using media. It is significant that the politicians should not be seen in television nearly before elections in order to have a fair exposure of politicians in mass media. The researchers would recommend that this study be further done through studying its content and would focus on the commercial and the endorsers who are involved in politics -- Author's abstract.